POVO TRADICIONAL POMERANO: CULTURAS, MEMÓRIAS E EDUCAÇÃO - Koeler, Edineia (2021)
This research investigates cultures, memories and education of the Traditional Pomeranian People (Decree 6.040/2007), to understand the means of production of Pomeranian life in its relationship with the community. We analyzed a memorial house in Alto Santa Maria, municipality of Santa Maria de Jetibá, Espírito Santo, Brazil. The question that guided the study was: Can we affirm that the ways of life of the Traditional Pomeranian People promote cultures, memories and educational practices? In addition, by cultural heritage we mean everything that has historical and cultural importance for a community, such as architecture, festivals, dances, music, popular manifestations, arts, cuisine, among others. We work with qualitative (FICHTNER et al., 2020) and co-research (BRANDÃO, 2003) approaches in carrying out observations and narrative interviews (JOVCHELOVITCH; BAUER, 2011). We dialogue with references about cultures (BRANDÃO, 1985, 2012), ethnicity (ARANHA, 2002; BARTH, 2011), orality (B , 2010; ONG, 1998) and neoautochthony (SAVEDRA; MAZZELLI-RODRIGUES, 2017). The investigations benefited from debates about “invention of traditions” (HOBSBAWM, 1997) and individual and collective memories (HALBWACHS, 1990; ASSMANN, 2016). Orality is a dimension to be further studied in Pomeranian culture. However, our data on narratives about the land, work, spirituality, festivals and education point out that Waiandt’s Huus contributes to the reinvention of the Pomeranian tradition and foster the cultures and memories of the Traditional Pomeranian People.